Performance studies on selected light weight power tillers - Narang, Suresh; Tiwari, P S (Journal of Agricultural Engineering, 2005)
Light weight power tillers have been recently introduced in the country. Most models of light weight power tillers being manufactured in India have been provided with a front or rear mounted powered rotary unit for forward movement as well as for tillage operation. In order to assess the performance of light weight power tillers under similar soil conditions, three models of light weight power tillers designated as A, B and C having front mounted rotary arrangement were evaluated for seedbed preparation, interculture operation and basin preparation. Heart rate responses and overall discomfort ratings of power tiller operators were also studied during above operations. The average effective field capacity of A, B, and C power tillers were 0.17, 0.15 and 0.16 ha/h, respectively for seedbed preparation during kharif season. Mean heart rate of the operators during operation of respective power tillers were 125.9, 121.8 and 132.6 beats/min and overall discomfort ratings on the 10-point VAD scale for operating duration of 15 min were 3.0, 2.6 and 3.75. The effective field capacity of power tiller A during interculture operation in rose plantation was 0.165 ha/h. Mean heart rate of the operator during interculture operation was 123.2 beats/min. The overall discomfort rating on the 10-point VAD scale for an operating duration of 30 min was 4.5. The effective field capacity of power tiller B during interculture operation in sugarcane crop was 0.149 ha/h. The mean heart rate of the operator was 129.1 beats/min. The average time required for basin preparation with power tillers A and C were 9.0 and 8.68 min/basin, respectively. The depth of loose soil inside the basin varied from 30 to 50 mm. The mean heart rates during basin preparation with power tiller A and C were 129.8 and 138.8 beats/min, respectively. The corresponding mean overall discomfort ratings after preparation of five basins were recorded as 5.1 and 5.5 on the 10- point VAD scale.